Total Parathyroidectomy with Subcutaneous Parathyroid Forearm Autotransplantation in the Treatment of Secondary Hyperparathyroidism: A Single-Center Experience - Claudio Casella; Alessandro Galani; Luigi Totaro; Silvia Ministrini; Silvia Lai; Mira Dimko; Nazario Portolani (International Journal of Endocrinology)
Introduction. Secondary hyperparathyroidism is common in chronic kidney disease. Parathyroidectomy is indicated in refractory hyperparathyroidism when medical treatments and so the parathyroid hormone levels cannot be lowered to acceptable values without causing significant hyperphosphatemia or hypercalcemia. The aim of this study is to compare the efficacy and safety of total parathyroidectomy with subcutaneous forearm autotransplantation with total parathyroidectomy with intramuscular forearm autotransplantation. Materials and Methods. A single-center retrospective cohort study of total parathyroidectomy with forearm autotransplantation from January 2002 to February 2013 was performed. According to the surgical technique, patients were divided into an intramuscular group (Group 1) and a subcutaneous group (Group 2). 38 patients with secondary hyperparathyroidism were enrolled; 23 patients were subjected to total parathyroidectomy with parathyroid tissue replanting in the subcutaneous forearm of the upper nondominant limb, while 15 patients were subjected to replanting in the intramuscular seat. Results. A total of 38 patients (56 ± 13 years) were enrolled. In both groups, the preoperative iPTH value was markedly high, 1750 ± 619 pg/ml in the intramuscular autotransplantation group and 1527 ± 451 pg/ml in the subcutaneous autotransplantation group (p=0.079). Transient hypoparathyroidism was shown in 7 patients, and 1 patient showed persistent hypoparathyroidism (p=0.387). 2 patients showed persistent hyperparathyroidism (p=0.816), and in 2 others was found recurrent hyperparathyroidism (p=0.816); 3 of them underwent autograftectomy. The anterior compartment of the forearm nondominant limb was sacrificed in 1 case of intramuscular autotransplantation with functional arm deficit. Conclusions. The efficacy and safety of parathyroid tissue autotransplantation in the subcutaneous forearm of the upper nondominant limb is confirmed with a good rate of tissue engraftment and with a comparable number of postsurgical transient and persistent hypoparathyroidism and hyperparathyroidism incidence in both techniques. Furthermore, this technique preserves arm functionality in the case of autograftectomy. Consequently, it is our opinion that total parathyroidectomy with subcutaneous forearm autotransplantation is currently the best choice.